2022
DOI: 10.1124/dmd.122.000877
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Modeling of Warfarin ІI – Model-Based Analysis of Warfarin Metabolites after Warfarin Administered Either Alone or Together with Fluconazole or Rifampin

Abstract: The objective of this study is to conduct a population pharmacokinetic (PK) model-based analysis on 10 warfarin metabolites (4'-, 6-, 7-, 8-and 10-hydroxylated (OH)-S-and Rwarfarin), when warfarin is administered alone or together with either fluconazole or rifampin.One or two compartment PK models expanded from target mediated drug disposition (TMDD) models developed previously for warfarin enantiomers were able to sufficiently characterize the PK profiles of 10 warfarin metabolites in plasma and urine under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Subjects possessing the CYP2C9 *2 and *3 variants experience higher S-warfarin exposure following warfarin administration and require lower warfarin maintenance doses (Dean, 2012). In subjects with the CYP2C9 *2 and *3 variants, non-CYP2C9 mediated elimination pathways occupy a higher proportion of overall S-warfarin elimination (Cheng et al, 2022b). A differential effect of fluconazole inhibition and rifampin induction on different metabolic pathways of S-warfarin was also noted, potentially explaining our observation of CYP2C9 genotype-dependent DDIs on S-warfarin PK in our previous population PK analysis (Cheng et al, 2022a).…”
Section: Population Simulationsmentioning
confidence: 51%
See 2 more Smart Citations
“…Subjects possessing the CYP2C9 *2 and *3 variants experience higher S-warfarin exposure following warfarin administration and require lower warfarin maintenance doses (Dean, 2012). In subjects with the CYP2C9 *2 and *3 variants, non-CYP2C9 mediated elimination pathways occupy a higher proportion of overall S-warfarin elimination (Cheng et al, 2022b). A differential effect of fluconazole inhibition and rifampin induction on different metabolic pathways of S-warfarin was also noted, potentially explaining our observation of CYP2C9 genotype-dependent DDIs on S-warfarin PK in our previous population PK analysis (Cheng et al, 2022a).…”
Section: Population Simulationsmentioning
confidence: 51%
“…The hepatic intrinsic CL values for S-and R-warfarin were separated into five metabolic pathways (4'-, 6-, 7-, 8-, 10-monohydroxylated (OH)) pathways. The proportion of each metabolite as a function of the overall clearance was based on the results of our previous warfarin metabolites population PK modeling study (Cheng et al, 2022b). The metabolic elimination of S-and Rwarfarin was assumed to be completely mediated by these five metabolic pathways.…”
Section: Incorporating Drug-drug Interactions Into Warfarin Pbpk Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the formation of 4-OH is the predominant ATX elimination pathway in CYP2D6 AS ≥ 0.5 patients, minor metabolic pathways dominate when CYP2D6 activity is compromised. 30,31 Frequently referred to as "shifting" or "shunting" in the literature, the issue is more related to loss of the quantitatively most important pathway. Consider a situation where CYP2D6, CYP2C19, and CYP2B6 are responsible for 75%, 15%, and 10% of the total clearance of a compound -in essence a "pie" of 100 units, with slices of 75, 15, and 10 units.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our analysis found that the contribution of 4‐OH to the overall metabolic elimination pathway decreased as the CYP2D6 AS (functional CYP2D6 activity) decreases ( Figure ). Although the formation of 4‐OH is the predominant ATX elimination pathway in CYP2D6 AS ≥ 0.5 patients, minor metabolic pathways dominate when CYP2D6 activity is compromised 30,31 . Frequently referred to as “shifting” or “shunting” in the literature, the issue is more related to loss of the quantitatively most important pathway.…”
Section: Discussionmentioning
confidence: 99%